Lactobacillus reuteri Inhibition of Enteropathogenic Escherichia coli Adherence to Human Intestinal Epithelium - Walsham, Alistair D. S.; MacKenzie, Donald A.; Cook, Vivienne; Wemyss-Holden, Simon; Hews, Claire L.; Juge, Nathalie; Schüller, Stephanie (Frontiers in Microbiology, 2016)
Enteropathogenic Escherichia coli (EPEC) is a major cause of diarrheal infant death in developing countries, and probiotic bacteria have been shown to provide health benefits in gastrointestinal infections. In this study, we have investigated the influence of the gut symbiont Lactobacillus reuteri on EPEC adherence to the human intestinal epithelium. Different host cell model systems including non-mucus-producing HT-29 and mucus-producing LS174T intestinal epithelial cell lines as well as human small intestinal biopsies were used. Adherence of L. reuteri to HT-29 cells was strain-specific, and the mucus-binding proteins CmbA and MUB increased binding to both HT-29 and LS174T cells. L. reuteri ATCC PTA 6475 and ATCC 53608 significantly inhibited EPEC binding to HT-29 but not LS174T cells. While pre-incubation of LS174T cells with ATCC PTA 6475 did not affect EPEC attaching/effacing (A/E) lesion formation, it increased the size of EPEC microcolonies. ATCC PTA 6475 and ATCC 53608 binding to the mucus layer resulted in decreased EPEC adherence to small intestinal biopsy epithelium. Our findings show that L. reuteri reduction of EPEC adhesion is strain-specific and has the potential to target either the epithelium or the mucus layer, providing further rationale for the selection of probiotic strains.